Strengthening Religious Tolerance with Islamic Views in the Era of Diversity in Indonesia - Idris, Muh; Willya, Evra; Mokodenseho, Sabil (Westscience Press, 2024)
This qualitative study delves into the dynamics of religious tolerance within the diverse societal fabric of Indonesia, with a particular focus on Islamic perspectives. Through interviews with 10 informants representing various religious backgrounds, the research elucidates the role of Islam in fostering tolerance amidst religious diversity. Key themes emerge, highlighting Islamic teachings on tolerance, challenges to religious harmony, and strategies for promoting interfaith understanding. While Islam emphasizes principles of acceptance and coexistence, the study uncovers persistent challenges such as the politicization of religion and the influence of extremist ideologies. Nevertheless, the findings underscore the agency of individuals and communities in promoting religious tolerance through dialogue, education, and community engagement initiatives. Ultimately, the study contributes to a nuanced understanding of the interplay between Islam and religious tolerance in Indonesia, offering insights for fostering a culture of inclusivity and respect in diverse societies.